La diversidad productiva en los procesos de desarrollo socioeconómico en la parroquia rural Uzhcurrumi, periodo 2024-2025 - Jimenez Guambaña, Lucila Roxana; Caceres Mina, Dayamara Yamilexi (Machala : Universidad Técnica de Machala, 2025)
This research work entitled "Productive diversity in the processes of socioeconomic development in the rural parish of Uzhcurrumi, period 2024-2025" analyzes the relevance of the diversification of economic activities as a central axis to improve the quality of life of the inhabitants of the parish belonging to the canton of Pasaje, province of El Oro. It is recognized that sustainable development in rural areas requires strategic use of available natural and human resources, through diverse production processes that respond to the particularities of the territory. The general objective of the research was to determine how productive diversity influences the socioeconomic development of the parish. To this end, specific objectives were proposed, such as identifying the types of production that are developed in the area, recognizing the sectors that contribute the most to family income, analyzing how these activities improve the quality of life, and examining their role in social cohesion. The data collected show a parish with multiple agricultural activities (mandarins, oranges, corn, cocoa, bananas), livestock (cattle, pigs, poultry and tilapia) and forestry (timber extraction), which constitute the basis of local economic sustenance. The methodology was framed in an empirical-inductive approach and also in the hypothetical-deductive approach, which allowed the integration of quantitative and qualitative information through research techniques such as surveys applied to a sample of the population, semi-structured interviews with parish and municipal authorities and finally a direct observation guide in the field. The results obtained showed that, although Uzhcurrumi has favorable agroecological conditions, there is a limited incorporation of technological innovation, little access to financing and a weak institutional articulation that hinders the strengthening of production processes. Theoretically, the research is based on the structural-functionalist perspective and the theory of modernization, highlighting how productive diversity fulfills essential social functions, contributing to economic stability, social inclusion and balanced territorial development. In 7 addition, the need to overcome the traditional model based on monocultures and move towards a more sustainable model, with the integration of ecological practices, strengthening community associativity and improving access to markets, is discussed. In this context, the study proposes an intervention aimed at promoting local capacities through technical training programs, promotion of rural enterprises, technical assistance and implementation of direct marketing strategies. These actions seek to consolidate endogenous development based on the active participation of social actors, the responsible use of natural resources and the strengthening of cooperation networks. In short, it is established that productive diversity is a fundamental strategy to achieve sustainable socio-economic development in Uzhcurrumi. Not only does it contribute to increased income and job creation, but it also strengthens cultural identity, community cohesion and resilience in the face of economic or climate crises. However, achieving these objectives requires the joint intervention of local governments, social organizations and citizens, to implement integrated policies that respect the environment, promote social equity and ensure better living conditions for current and future generations.
El presente trabajo de investigación titulado “La diversidad productiva en los procesos de desarrollo socioeconómico en la parroquia rural Uzhcurrumi, periodo 2024-2025” analiza la relevancia de la diversificación de las actividades económicas como eje central para mejorar la calidad de vida de los habitantes de la parroquia perteneciente al cantón Pasaje, provincia de El Oro. Se reconoce que el desarrollo sostenible en áreas rurales requiere aprovechar de manera estratégica los recursos naturales y humanos disponibles, mediante procesos productivos diversos que respondan a las particularidades del territorio. El objetivo general de la investigación fue determinar cómo influye la diversidad productiva en el desarrollo socioeconómico de la parroquia. Para ello, se plantearon objetivos específicos como identificar los tipos de producción que se desarrollan en la zona, reconocer los sectores que aportan más al ingreso familiar, analizar cómo estas actividades mejoran la calidad de vida y examinar su papel en la cohesión social. Los datos recopilados evidencian una parroquia con múltiples actividades agrícolas (mandarina, naranja, maíz, cacao, banano), pecuarias (reses, porcinos, aves de corral y tilapia) y forestales (extracción de madera), que constituyen la base del sustento económico local. La metodología se enmarcó en un enfoque empírico-inductivo y también en el hipotéticodeductivo, lo cual permitió integrar información cuantitativa y cualitativa mediante técnicas de investigación como encuestas aplicadas a una muestra de la población, entrevistas semiestructuradas a autoridades de la parroquia y del municipio y por último una guía de observación directa en campo. Los resultados obtenidos demostraron que, si bien Uzhcurrumi cuenta con condiciones agroecológicas favorables, existe una limitada incorporación de innovación tecnológica, escaso acceso a financiamiento y una débil articulación institucional que dificulta el fortalecimiento de los procesos productivos. Teóricamente, la investigación se apoya en la perspectiva estructural-funcionalista y en la teoría de la modernización, destacando cómo la diversidad productiva cumple funciones sociales esenciales, contribuyendo a la estabilidad económica, la inclusión social y el 5 desarrollo territorial equilibrado. Además, se discute la necesidad de superar el modelo tradicional basado en monocultivos y avanzar hacia un modelo más sostenible, con integración de prácticas ecológicas, fortalecimiento de la asociatividad comunitaria y mejoramiento del acceso a mercados. En este contexto, el estudio propone una intervención orientada a promover capacidades locales mediante programas de formación técnica, fomento a emprendimientos rurales, asistencia técnica e implementación de estrategias de comercialización directa. Estas acciones buscan consolidar un desarrollo endógeno basado en la participación activa de los actores sociales, el aprovechamiento responsable de los recursos naturales y el fortalecimiento de las redes de cooperación. En pocas palabras se establece que la diversidad productiva constituye una estrategia fundamental para alcanzar un desarrollo socioeconómico sostenible en Uzhcurrumi. No solo contribuye al incremento de ingresos y generación de empleo, sino que fortalece la identidad cultural, la cohesión comunitaria y la resiliencia frente a crisis económicas o climáticas. No obstante, alcanzar estos objetivos requiere la intervención conjunta de los gobiernos locales, organizaciones sociales y ciudadanía, para implementar políticas integradas que respeten el entorno, promuevan la equidad social y aseguren mejores condiciones de vida para las actuales y futuras generaciones.
Keywords: DIVERSIDAD PRODUCTIVA; DESARROLLO SOCIOECONÓMICO; UZHCURRUMI